Uji Organoleptik Kue Stik Dari Kombinasi Tepung Terigu Dan Tepung Gayam Dengan Perbandingan Berbeda - TRIWIRAT SAPUTRI, AYUK, Dra. Hj. Suparti, M.Si, Siti Chalimah, Dr. Mpd (2016)
The Gayam plant is a local plant that contains the good nutrision and useful for health. The gayam has not been used maximally by society because it is considered less luctrative and difficult to be culvited, then the researcher interetsed to increase the used of Gayam with comparasion wheat flour become the product has been precious economic like as Stik product. This research purpose for knowing the proteint contents and quality of stik that combination of wheat flour and gayam flour with using comparasion. This research used RancanganAcakLengkap (RAL) factorial polaand one treat ment factor away. The first factor is the comparasion of wheat flour : gayam flour ( K ) that is yaitu K1= 5 : 1,0; K2= 2,5 : 1,5; K3 = 2,5 : 2,0; K4 =2,5 : 2,5; K5 = 3,0 : 1,0; K6 = 3,0 : 1,5; K7 = 3,0 : 2,0; K8 = 3,0 : 2,5; K9 = 3,5 : 1,0; K10 = 3,5 : 1,5; K11 = 3,5 : 2,0; K12 = 3,5 : 2,5; K13 = 4,0 : 1,0; K14 = 4,0 : 1,5; K15 = 4,0 : 2,0 dan K16 = 4,0 : 2,5. The observed parameter is the proteint contents and quality of stik include the color, aroma, taste, and teksture with the capacity acceptance. The acceptance capacity of society form of the willingness to received a result of product. Research result indicate that the society can received the inovation of wheat flour and gayam flour stik.. The most good acceptance capacity of society that is K16 treatment wheat flour :gayam flour (4:2,5) as big as 2,8.